2013
DOI: 10.1177/1934578x1300800637
|View full text |Cite
|
Sign up to set email alerts
|

Aconitamide, a Novel Alkaloid from the Roots of Aconitum carmichaeli

Abstract: Aconitum carmichaeli Debx. is a traditional Chinese medicine commonly employed for curing a wide array of diseases in East Asia. From the ethyl acetate soluble fraction of the methanolic extracts of A. carmichaeli, a new alkaloid, aconitamide (1), along with eighteen known compounds 2-19 were isolated by column chromatography and identified on the basis of spectroscopic analyses. The anti-telomerase activity of 1-19 was also assessed, but no activity was found, even at a concentration higher than 30 M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A quaternary carbon ( δ C 134.4 s) ortho to the methyl ester was assigned to connect with the N-atom of the amide group, which caused strong hydrogen bonding between –NH ( δ H 11.94, s) and the carbonyl of the ester [ 11 ]. Similarly, the downfield shift of OH-2 ( δ H 12.34, s) caused by intramolecular hydrogen bonding between the amide carbonyl and OH-2′ suggested that the amide group connected with C-1′, which was further supported by the HMBC correlation from H-6′ to C-7′ and the ROESY correlation between H-6 and –NH [ 12 ]. Therefore, the structure of compound 2 was determined as stapfianine B, with its assigned NMR spectroscopic data listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A quaternary carbon ( δ C 134.4 s) ortho to the methyl ester was assigned to connect with the N-atom of the amide group, which caused strong hydrogen bonding between –NH ( δ H 11.94, s) and the carbonyl of the ester [ 11 ]. Similarly, the downfield shift of OH-2 ( δ H 12.34, s) caused by intramolecular hydrogen bonding between the amide carbonyl and OH-2′ suggested that the amide group connected with C-1′, which was further supported by the HMBC correlation from H-6′ to C-7′ and the ROESY correlation between H-6 and –NH [ 12 ]. Therefore, the structure of compound 2 was determined as stapfianine B, with its assigned NMR spectroscopic data listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated a regulatory effect of SBT and Stig on immunosuppression using an established murine model of CTX-induced immunosuppression ( Figure 7 A). Each dose was determined by an MTT assay ( Figure 2 A) with reference to the previous reports [ 18 , 21 , 51 , 52 , 53 , 54 , 55 ]. As shown in Figure 7 B,C, the CTX control group showed remarkably reduced body weight gains and spleen index compared to the normal group ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…SBT was reported to treat heart failure and septic shock [ 15 , 16 ]. Stigmasterol (Stig) was reported to be an active compound of both Panax ginseng and Aconitum carmichaeli [ 17 , 18 ]. We thus selected Stig, the shared component of Panax ginseng and Aconitum carmichaeli , as the active compound of SBT in this study.…”
Section: Introductionmentioning
confidence: 99%